2010
DOI: 10.1210/me.2009-0152
|View full text |Cite
|
Sign up to set email alerts
|

Early Hepatic Insulin Resistance in Mice: A Metabolomics Analysis

Abstract: When fed with a high-fat safflower oil diet for 3 wk, wild-type mice develop hepatic insulin resistance, whereas mice lacking glycerol-3-phosphate acyltransferase-1 retain insulin sensitivity. We examined early changes in the development of insulin resistance via liver and plasma metabolome analyses that compared wild-type and glycerol-3-phosphate acyltransferase-deficient mice fed with either a low-fat or the safflower oil diet for 3 wk. We reasoned that diet-induced changes in metabolites that occurred only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 31 publications
13
46
0
Order By: Relevance
“…This effect was also observed in KK-Ay mice, which showed increased levels of CA, DCA, TCA and TDCA in liver and intestine, which were also observed in our study in cecal samples of C57J mice fed with a HFD (Watanabe et al, 2006). The patterns of TBAs can be modulated through diet, absence of bacteria, distinct microbiome community, BAs or farnesoid X receptors agonists (Claus et al, 2008;Li et al, 2010a;Swann et al, 2011;Watanabe et al, 2011). In this study, lower abundance of TBAs in cecum of C57N mice could also be explained through an increase in their deconjugation rate by specific gut bacteria that are using the sulfur-containing taurine as an energy source such as Enterobacteria or Bacteroides spp.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This effect was also observed in KK-Ay mice, which showed increased levels of CA, DCA, TCA and TDCA in liver and intestine, which were also observed in our study in cecal samples of C57J mice fed with a HFD (Watanabe et al, 2006). The patterns of TBAs can be modulated through diet, absence of bacteria, distinct microbiome community, BAs or farnesoid X receptors agonists (Claus et al, 2008;Li et al, 2010a;Swann et al, 2011;Watanabe et al, 2011). In this study, lower abundance of TBAs in cecum of C57N mice could also be explained through an increase in their deconjugation rate by specific gut bacteria that are using the sulfur-containing taurine as an energy source such as Enterobacteria or Bacteroides spp.…”
Section: Discussionsupporting
confidence: 85%
“…Many of these studies investigated the particular role of metabolites in inflammatory bowel diseases by using primarily NMR studies (Lin et al, 2011). Non-targeted metabolomics approaches in gut microbial sample matrices and liver, analysing changes occurring in metabolic diseases like obesity, are rarely given, but many studies addressed obesity-related metabolome characterization (Dumas et al, 2006;Williams et al, 2006;Fearnside et al, 2008;Li et al, 2008Li et al, , 2010aShearer et al, 2008;Newgard et al, 2009;Waldram et al, 2009;Kim et al, 2009Kim et al, , 2010Kim et al, , 2011Calvani et al, 2010;Xie et al, 2010Xie et al, , 2012Zhao et al, 2010;Oberbach et al, 2011;Duggan et al, 2011a,b;Jung et al, 2012;Hanhineva et al, 2013;Schäfer et al, 2014;Seyfried et al, 2013;Won et al, 2013;Xu et al, 2013;Daniel et al, 2014;Eisinger et al, 2014). Comparing with other studies, our study provides a greater insight into different metabolite classes that were involved in obesity-related changes by reflecting both bacterial and host metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was blocked by previous incubation with the BKB2R antagonist HOE140. These results are similar to those observed after BK injection in the portal vein in vivo (Figure 6), suggesting that the chronic effects of BK in obB2KO mice are also dependent on other systems as suggest by Li et al, 45 who showed a cross talking between the KKS and the insulin pathway, 45 and other several studies that show the influence of BK in insulin secretion of the pancreatic cells. [46][47][48][49] It is important to highlight that this finding was only observed in cells that were FBS starved during 6 h and were also stimulated with cAMP, the second messenger of the glucagon receptor pathway.…”
Section: Discussionsupporting
confidence: 88%
“…43 All these results are in consonance with Hartl et al, 44 who proposed that the favorable effects of systemic administration of kinins in humans could be mediated by prostaglandins. On the other hand, diet induced liver-insulin-resistance in rats was followed by decreased plasma BK level in a metabolomic analysis 45 suggesting that the insulin pathway could be involved in metabolic effect of BK in vivo. Although it is unclear whether the mechanism is insulin dependent or not, the present work shows that the KKS is involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Functional interpretation of this change, however, is meaningful only in the context of the large metabolic flux of glutamate release and recycling taking place in glia and neurons (36,37). Furthermore, it must be noted that glutamate concentrations in tissues other than brain were previously shown to be affected by diet and exercise (38,39). Although such an environmental effect cannot be fully excluded in our study, human-specific changes in glutamate metabolism are intriguing, and might be an interesting and important subject of further research.…”
Section: Discussionmentioning
confidence: 99%